Radiation shielding study of tungsten impact on tellurite-bismuth based glasses - Kh.A. Bashar; M.F.N. Jaafar; Y. Mansur; S.O. Baki; M.A. Mahdi (Chemical Physics Impact)
The current study, a new Pb-free glasses of host (H) and four samples (S1-S4) of tellurite-bismuth-tungsten oxide according to formula: (70-x) TeO2–10Bi2O3–10ZnO-10Al2O3- xWO3, x = 0, 5, 10, 15, 20 mol %, were prepared by traditional melt-quenching method. The phase formation of all samples is analyzed by XRD (x-ray diffraction) were found they are without any crystallization network. Some physical properties like density and molar volume were estimated as well. Within energy of 0.015MeV-15MeV, samples are investigated in terms of gamma ray radiation shielding features. The MCNP5 stimulation code and theoretical XCOM software in addition to the other relevant equations are implemented to determine the mass attenuation coefficient (MAC) values where the other parameters are identified depending on its value such as mean free path (MFP), effective atomic number (Zeff) and half-value layer (HVL). Also, the exposure build factor (EBF) and energy absorbed build factor (EABF) are evaluated by the geometric progression (G-P) fitting method. The appearance of synthesized glasses reflects that, the increment of WO3 contents leads to increase the glasses opacity due to their density between 3.532 - 3.912 g/cm3. The uncertainty concentrations of the samples are calculated were they emphasized the accuracy of glass compositions. Moreover, the calculation results of stimulated MCNP5 code and theoretical XCOM program are closely matched, as the difference between them can be neglected. Further, the comparison with other works is made which emphasized the enhancement of the findings. Finally, according to above merits and results, the effectiveness of the radiation shielding features can be obviously recognized which is due to the WO3 incorporated concentrations.